anonymous
  • anonymous
PLEASE HELP :3 Solve 2x + 5y = −13 3x − 4y = −8 (4, 1) (−4, 1) (4, −1) (−4, −1)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
@Jack1 for ones like these: there is no parenthesis, or exponents, so I staret with the multiplication.. I want to get my y's to one side.. how do I do that? I divide them?
Jack1
  • Jack1
i like to subtract first to isolate the one term on one side so 2x + 5y = −13 2x = -13 -5y x = -(13/2) - (5/2)y
Jack1
  • Jack1
or if not, get them both in terms of 6x

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Jack1
  • Jack1
2x + 5y = -13 so 6x + 15y = -39 and 3x - 4y = -8 so 6x - 8y = -16 therefore 6x = -39 - 15y and 6x = -16 + 8y
anonymous
  • anonymous
AH I thought so, u do them apart and I knew I took the 5 from that side
Nurali
  • Nurali
2x + 5y = −13-------(1) 3x − 4y = −8 --------(2) in equation 1 2x=-13-5y x=-13-5y/2 put x in equation 2 3(-13-5y/2)-4y=-8 -39-15y/2-4y=-8 -39-15y-8y=-16 -23y=-16+39 -23y=23 y=-1 put y in equation 1 2x + 5y = −13 2x+5(-1)=-13 2x-5=-13 2x=-13+5 2x=-8 x=-4
Jack1
  • Jack1
6x = -39 - 15y = -16 + 8y -39 - 15y = -16 + 8y -39 = -16 + 23y -23 = 23y -1 = y
anonymous
  • anonymous
I see.
anonymous
  • anonymous
The next one I have I have to get the value of y.. is it the same way we get the value of x?
Jack1
  • Jack1
exactly the same way, it doesn't matter if the term is called x or y or q, its all the same when using simultaneous equations
anonymous
  • anonymous
Ok I think I gotcha
anonymous
  • anonymous
What is the value of y in the solution to the following system of equations? 5x − 3y = −11 2x − 6y = −14 −1 0 1 2
anonymous
  • anonymous
This is what I have. ill let u no what I get
Jack1
  • Jack1
cools
anonymous
  • anonymous
ok so I got
anonymous
  • anonymous
5x-3y=-11 +3y ____________ 5x=-11+3y
anonymous
  • anonymous
correct?
uri
  • uri
where is +3y coming from?
Jack1
  • Jack1
yep
Jack1
  • Jack1
ignore uri, he's a little slow and apparently i hate him ;D
anonymous
  • anonymous
Oh..
uri
  • uri
Huh? I'm a girl..and that's not the way to talk.
anonymous
  • anonymous
Where do I go from 5x=-11+3y
Jack1
  • Jack1
sure u are... online anyway an i bet u tell that to all the boys ;P
uri
  • uri
Ah? last time i checked..i was a girl.
Jack1
  • Jack1
double it change it to 10x
anonymous
  • anonymous
..... sooo no one is going to help me but we will argue on my question?... Thanks guys
anonymous
  • anonymous
Now your confusing me and not helping me
Jack1
  • Jack1
5x=-11+3y 10x = -22 + 6
uri
  • uri
You are not even teaching her the right thing.Also,You are very mean and you don't know how to respond to someone..when they ask you a question. I might link you this:http://openstudy.com/code-of-conduct Next time if you're mean to me.I'll report you to Preetha. @Jack1
Jack1
  • Jack1
so thats equation 1 in a form we can use now for equation 2: 2x − 6y = −14 change it so u get 10x on one side
Jack1
  • Jack1
sorry, back to equation 1: it should be 10x = -22 + 6y, not 10x = -22 + 6, my bad now equation 2: 2x − 6y = −14 (times 5) 10x - 30y = -70 (add 30y to both sides) 10x - 30y + 30y = -70 + 30y 10x = -70 + 30y
Jack1
  • Jack1
so equation 1 is now 10x = -22 + 6y and equation 2 is now 10x = -70 + 30y so 10x = -22 + 6y = -70 + 30y -22 + 6y = -70 + 30y can u solve from here?
thomaster
  • thomaster
Jack1
  • Jack1
@raebaby420
uri
  • uri
Huehue.
Jack1
  • Jack1
god u are such a girl XP
uri
  • uri
You called me a boy dat mad me cry..:3
uri
  • uri
made*
Jack1
  • Jack1
im sorry i called u a boy, i was jus playing and i took it too far, my bad
uri
  • uri
It's alright.

Looking for something else?

Not the answer you are looking for? Search for more explanations.